Linguistic refactoring of business process models - Pittke, Fabian (Logos Verlag Berlin, 2016)
Long description: In the past decades, organizations had to face numerous challenges due to intensifying globalization, shorter innovation cycles and growing IT support. Business process management is seen as a comprehensive approach to address these challenges. For this purpose, business process models are increasingly utilized to document and redesign relevant parts of the organization's business operations. Since organizations tend to have a huge number of such models, analysis techniques are required that ensure the quality of these process models in an automatic fashion. The goal of this doctoral thesis is the development of model refactoring techniques by integrating and applying concepts from the three main branches of theoretical linguistics: syntax, semantics, and pragmatics. The syntactical refactoring technique addresses linguistic issues that arise by expressing process behavior with natural language. The semantic refactoring technique reworks terminology with overlapping and synonymous meaning. The pragmatic refactoring technique provides recommendations for incompletely specified process models. All of the presented techniques have been evaluated with real-world process model repositories from various industries to demonstrate their applicability and efficiency.